Elevated cytokine, chemokine, and growth and differentiation factor-15 levels in hemorrhagic shock and encephalopathy syndrome: A retrospective observational study. (January 2021) - Yamaguchi, Hiroshi; Nishiyama, Masahiro; Tokumoto, Shoichi; Ishida, Yusuke; Tomioka, Kazumi; Aoki, Kazunori; Seino, Yusuke; Toyoshima, Daisaku; Takeda, Hiroki; Kurosawa, Hiroshi; Sakuma, Hiroshi; Tada, Hiroko; et al.
Highlights: Highest cytokine and chemokine levels were noted in the first 24 h in HSES. GDF-15 levels were significantly higher in patients with HSES in the first 24 h. The levels of IL-2 and IL-4 did not differ between HSES patients and controls. Abstract: Patients with hemorrhagic shock and encephalopathy syndrome (HSES) have a high early mortality rate, which may be caused by a 'cytokine storm'. However, there is little information on how cytokines and chemokines change over time in these patients. We aimed to describe the characteristics of HSES by examining changes in serum biomarker levels over time. Six patients with HSES were included. We retrospectively evaluated their clinical course and imaging/laboratory data. We measured serum levels of multiple cytokines [interleukin 1β (IL-1β), IL-2, IL-4, IL-6, IL-10, IL-17, interferon-gamma, and tumor necrosis factor alpha], chemokines (IL-8, monocyte chemoattractant protein-1, interferon-inducible protein-10), and growth and differentiation factor (GDF)-15. The highest cytokine and chemokine levels were noted in the first 24 h, and decreased thereafter. The GDF-15 level was markedly high. Cytokine, chemokine, and GDF-15 levels were significantly higher in patients with HSES than in controls in the first 24 h, except for IL-2 and IL-4. Patients with HSES have high inflammatory cytokine and chemokine levels, a high GDF-15 level in the first 24 h, and high lactate levels. Our study provides new insights on the pathophysiology of HSES, a detailed clinical picture of patients with HSES, and potential biomarkers.